Keragaan Karakter Agronomi Beberapa Aksesi Bawang Merah (Allium ascalonicum L.) di Kabupaten Karawang - Nurul Umairoh; Elia Azizah; Rika Yayu Agustini (Faculty of Agriculture University of Singaperbangsa Karawang, 2023)
The use of various accessions in the same growing environment will give an idea of adaptability of accessions to be planted in Karawang Regency so that they have a better appearance of agronomic character. The research was carried out in an experimental field at the Faculty of Agriculture, Singaperbangsa Karawang University, which is located in Pasirjengkol Village, Majalaya District, Karawang Regency, West Java Province with an altitude of 40 m above sea level. The research was conducted in October – December 2021. The research method used an experimental method with a single factor Randomized Block Design (RAK). There were 8 treatments and it was repeated 4 times, so there were 32 experimental plots. Data were analyzed using analysis of variance and further tested with Duncan Multiple Range Test (DMRT) at 5% level. The results of this experiment showed that V6 (Berlind accessions) gave the highest number of tillers aged 35 DAP (10,10 tillers), number of tillers aged 42 DAP (12,90 tillers), number of tillers aged 49 DAP (14,10 tillers), number of tillers aged 56 DAP (14,55 tillers), number of tillers aged 63 DAP (16,95 tillers), wet weigth of tubers per plant (33,71 grams), wet weight of tubers per plot (163,75 grams). This research is expected to increase knowledge about the agronomic due to the accession of shallot in Karawang Regency. In addition, the result of this experiment can be applied to the cultivation of shallot in Karawang Regency.